Reflection on Conducting Qualitative Research: Principal Issues and Practical Solutions in Indonesia - Dewi Wardah Mazidatur Rohmah; Nuraziza Aliah (Journal on Education, 2023)
Every year, a large number of senior university students in Indonesia will/ have experience in conducting qualitative research. Some of them choose qualitative research because they understand that their questions only can be answered through qualitative research. While the rest of them only see that qualitative research is may be simpler than quantitative research because no need to calculate the numbers and do statistical trial. Unfortunately, many of these students who start their new role as novice researchers don’t have sufficient knowledge on some issues before doing this research. This paper aims to provide clear and practical elaboration of some principles in qualitative research which are frequently absent and become the common malpractices by novice researchers. Some practical solutions are discussed as well. In the end, conducting ideal qualitative research in Indonesia is not only the responsibility of expert researchers but also stakeholders, lecturers, and students.